2016
DOI: 10.18869/acadpub.jafm.68.224.23982
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Mixed Convection Fluid Flow, Heat Transfer and Entropy Generation in Triangular Enclosure Filled with a Nanofluid

Abstract: In this paper, mixed convection fluid flow, heat transfer and entropy generation inside a triangular enclosure filled with CuO-water nanofluid with variable properties are investigated numerically. The inclined walls of enclosure are maintained at a constant temperature T c . The moving bottom wall is kept at a constant temperature T h , which T h >T c .The numerical simulation of mixed convection is carried out using a computer program (FORTRAN language) based on finite volume method and SIMPLER algorithm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…They found that the effect of the enclosure angle is negligible on lines of current and temperature in small Rayleigh numbers, while free convection considerably increases in large Rayleigh numbers. In [19], authors numerically investigated a mixed convection fluid flow, heat transfer and entropy generation inside a triangular enclosure filled with CuO-water nanofluid with variable properties.…”
Section: Nomenclature P Rmentioning
confidence: 99%
“…They found that the effect of the enclosure angle is negligible on lines of current and temperature in small Rayleigh numbers, while free convection considerably increases in large Rayleigh numbers. In [19], authors numerically investigated a mixed convection fluid flow, heat transfer and entropy generation inside a triangular enclosure filled with CuO-water nanofluid with variable properties.…”
Section: Nomenclature P Rmentioning
confidence: 99%